The relationship between health-related quality of life and academic success in nursing students: the mediating role of academic burnout and academic motivation - Fatemeh Torkani; Seyed-Hasan Ahmadi; Alireza Binazir; Marjan Moradi Fath; Navid Shafigh; Hanieh Asadiparvar-Masouleh; Parvaneh Vasli (BMC Medical Education)
Abstract Background The identification of the key factors that affect academic success in nursing students, including health-related quality of life, academic burnout, and academic motivation, has been of the utmost importance to date. In this context, the present study sought to examine the relationship between health-related quality of life and academic success, with academic burnout and academic motivation mediating that relationship. Methods This analytical cross-sectional study included 262 eligible nursing students selected through convenience sampling from the School of Nursing and Midwifery at Shahid Beheshti University of Medical Sciences, Tehran, Iran. To evaluate health-related quality of life, academic burnout, and academic motivation, the 12-item Short Form Health Survey, the Academic Motivation Scale, and Breso’s Academic Burnout Scale were administered, respectively. The study achieved a 95% response rate. Academic success was assessed using the nursing program grade point average. Data analysis was conducted using SPSS Statistics (version 26) and Mplus (version 6.12) software, with a significance level set at 0.05. Results The findings of the study indicated that although health-related quality of life did not directly affect academic success, it could potentially enhance academic success through the mediation of intrinsic motivation (B = 0.005, 95% CI = -0.01 to 0.005, p ≤ 0.05). Furthermore, health-related quality of life can increase academic success through the mediation of academic burnout and intrinsic motivation (B = 0.013, 95% CI = 0.005 to 0.02, p ≤ 0.01). This indicates that academic burnout and intrinsic motivation significantly mediate the path from the health-related quality of life to academic success. Conclusions The study findings indicate that nursing education planners and instructors should develop and implement appropriate measures to enhance academic success in nursing students. These measures should also promote their health-related quality of life, academic motivation, and reduce academic burnout.